2018
DOI: 10.1038/s41598-018-27188-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of printing orientation on the electrochemical behaviour of 3D printed acrylonitrile butadiene styrene (ABS)/carbon black electrodes

Abstract: Additive manufacturing also known as 3D printing is being utilised in electrochemistry to reproducibly develop complex geometries with conductive properties. In this study, we explored if the electrochemical behavior of 3D printed acrylonitrile butadiene styrene (ABS)/carbon black electrodes was influenced by printing direction. The electrodes were printed in both horizontal and vertical directions. The horizsontal direction resulted in a smooth surface (HPSS electrode) and a comparatively rougher surface (HPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 20 publications
2
93
0
Order By: Relevance
“…Solidification of each layer is principally based on crystallization and chain entanglement of the polymer, however, addition of additive materials can affect the properties and solidification process of the matrix polymer. Common additives used in polymer matrix for EESDs are various conductive materials like ABS/graphene [26], ABS/carbon [27], PLA/graphene [28] and even PLA/LTO/carbon and PLA/LFP/carbon [29]* which are essential for electrode fabrication in lithium ion batteries. A good example is a recent study [30]** where three conductive agents (Super-P, MWCNTs, graphene) and two active materials (Lithium titanate, lithium manganese oxide) were blended with PLA to test the printability, conductivity and charge storage capacity of the new composite.…”
Section: Materials and Methods Considerationmentioning
confidence: 99%
“…Solidification of each layer is principally based on crystallization and chain entanglement of the polymer, however, addition of additive materials can affect the properties and solidification process of the matrix polymer. Common additives used in polymer matrix for EESDs are various conductive materials like ABS/graphene [26], ABS/carbon [27], PLA/graphene [28] and even PLA/LTO/carbon and PLA/LFP/carbon [29]* which are essential for electrode fabrication in lithium ion batteries. A good example is a recent study [30]** where three conductive agents (Super-P, MWCNTs, graphene) and two active materials (Lithium titanate, lithium manganese oxide) were blended with PLA to test the printability, conductivity and charge storage capacity of the new composite.…”
Section: Materials and Methods Considerationmentioning
confidence: 99%
“…[56,68] They have been utilized in various 3D printing techniques (extrusion-based, inkjet printing, IJP; selective laser sintering (SLS)) in the form of polymer-based conductive composites used for fabrication of electrically conductive structures, supercapacitor electrodes, Li-ion battery electrodes. [68][69][70][71][72] Carbon nanotubes are promising candidates for current collector and electrode 3D printing due to high carrier mobility, superior mechanical strength and large specific surface area that can be functionalized for improved energy storage performance. [73,74] Depending on the structure, CNT can be either conductors or semiconductors.…”
Section: Conductive Materials and Cell Casingmentioning
confidence: 99%
“…This methodology was adopted to make use of the priming filament that is typically discarded during print set-up. An additional advantage is that the filament is not impacted by print orientation, which Patel et al showed influenced heterogeneous electron transfer (HET) kinetics [48]. The diameter of the extruded material is approximately 0.6 mm under the settings employed.…”
Section: Electrode Preparation and Fabricationmentioning
confidence: 99%